Resíduos de agrotóxicos prejudicam o comportamento anti predatório em peixes - Pompermaier, Aline (2019)
Contamination of water bodies and groundwater is a reality. Antropic activities are responsible for the presence of pesticide residues in the water. This presence is due to the incorrect disposal of the packaging, leaching of the crops, direct application, besides the natural processes of degradation. Allied to this, Brazil is the largest consumer of pesticides in the world and herbicides are the best-selling class in the country. The effects of these substances on non-target organisms are still unknown. Using the experimental model Zebrafish (Danio rerio) we aimed to simulate the exposure of a non-target organism to pesticide residues and to mitigate the action of a predator to evaluate the anti-predatory response of the fish. The present study was carried out at the Laboratory of Fish Physiology of the Faculty of Agronomy and Veterinary Medicine of the University of Passo Fundo. The fish were exposed for 30 minutes in 10% of the CL 50 of the 2,4-D pesticides, Atrazine + Simazine, Glyphosate and Methylbenzoate. After the exposure the fish were placed individually in the acclimatization apparatus for 5 minutes, after which the first predatory stimulus was performed and the fish response was followed for 5 minutes. A second simulation was performed and the fish response was observed for another 5 minutes. Two control groups were used to compare the responses of the fish, NSC (No stimulus control), that received no stimulus, was only exploring the apparatus and SC (stimulus control) that received the same stress as the exposed group. Fish exposed to 2,4-D and glyphosate herbicides had their anti predatory response impaired. These animals stayed longer in the area of risk, which shows that pesticides interfered in their ability to perceive risk. Our results highlight the dangers and environmental consequences of the contamination of water bodies by pesticide residues that can affect aquatic life and damage the ecological balance.